The effect of stocking density ratio of fish on water plant productivity in aquaponics culture system - YULI ANDRIANI; YAYAT DHAHIYAT; ZAHIDAH ZAHIDAH; IRFAN ZIDNI (Nusantara Bioscience, 2017)
Andriani Y, Dhahiyat Y, Zahidah, Zidni I. 2016. The effect of stocking density ratio of fish on water plant productivity in aquaponics culture system. Nusantara Bioscience 8: xxxx. This study aims to determine the productivity of water plants at various stocking density ratios in the aquaponic culture system. This study is conducted experimentally using the Completely Randomized Design with the differences in the treatment of stocking density ratio, each repeated five times. The treatments of the stocking density ratio of both the catfish fry and the Nile tilapia fry include: A (75:75 fry/m2), B (100:50 fry/m2, and C (125:25 fry/m2). The observed parameters are 1) plant productivity including measuring the growth of water spinach and growth rate, covering weight gain, stem length and number of leaves, and 2) water quality, including dissolved oxygen (DO), nitrate and phosphate. The data of plant productivity is analyzed descriptively while the water quality is analyzed using ANOVA. The result of this study shows that the stocking density ratio significantly affects the productivity of water plants and the water quality of the media. The highest productivity of water spinach productivity occurs at the stocking density ratio of 75 catfish fry/m2: 75 Nile tilapia fry m2, at which the average stem length is 59.14 cm, average number of leaves is 13.67, and the harvest weight is 465 g. Fish stocking density ratio also affects the quality of water, where the synergy between fish farming and water plant growing results in the better water quality compared to fish farming without water plant. The highest quality of water is achieved at the stocking density ratio of 100 catfish fry/m2: 50 Nile tilapia fry/m2.